Physarella oblonga-centered bioassays for testing the biological activity of myxomycetes - Herrera Loaiza, Natalia Andrea (2011)
To study the trypanocidal, antibacterial, antifungal activity and cytotoxicity of myxomycetes, a rapid assessment focused on the species Physarella oblonga was carried out. Optimum conditions for culturing were utilized to develop a protocol that was adequate for bioanalysis of chemical compounds. Nuclear magnetic resonance (NMR) and mass spectroscopy (MS) detected the presence of stigmasterol and fatty acids in plasmodial extracts of Ph. oblonga through H1 analysis. These plasmodial extracts showed low toxicity and positive activity against epymastigote forms of Trypanosoma cruzi. This activity was significantly higher than the activity shown by one of the controls used. Similarly, the extracts from an unidentified species of myxomycete showed strong antimicrobial and antifungal activities against isolated strains of Bacillus cereus, Fusarium oxysporum and Rhizoctonia solani, whereas the myxomycete Physarum melleum displayed growth inhibition of the phytopathogen F. oxysporum. These results showed that with the use of an appropriate methodology, bioprospective analysis can be carried out on myxomycetes. In addition, this is apparently the first report on the antifungal and antiparasitic potential of myxomycetes